What Islam Did For Us : Understanding Islam's Contribution to Western Civilization (Watkins Publishing, 2006)
In these troubled times, when Islam is under seemingly perpetual attack, it is imperative to consider how much the West owes to the religion’s spiritual insights. Bestselling author Tim Wallace-Murphy presents the first major popular book to examine the common roots of Judaism, Christianity, and Islam and to reveal Islam’s immense contributions to our society—which included laying the foundations for our systems of education, astronomy, mathematics, and architecture. He also illustrates how the European Western powers helped foment the current crisis in the Middle East, and why we must strive for a just, equitable solution to these problems. Understanding can begin with this compelling acknowledgment of our shared spiritual heritage, including religious tolerance, respect for learning, and the concepts of chivalry and brotherhood.